(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Humans are social beings with basic rights. Human development requires these rights. Human rights are inalienable. Humans need privacy for peace, harmony, and physical internment. Privacy problems have always been debated. Protecting one’s body and home comes first. It soon moved towards personal information management. In a landmark 1891 paper, American attorneys Samuel Warren and Louis Brandeis defined privacy as the right to be alone. Alan Westin’s 1967 book, Privacy and Freedom, redefined privacy. Westin claimed that privacy is the right of individuals, organizations, and institutions to control the sharing of their information. Humans always sought privacy. History shows that privacy and technology are closely related. Cameras started contemporary debates. It grew to include computer production and use in an information technology that maintains everyone’s personal data. Privacy loss and surveillance are major concerns.Nowadays, technology is being used more to fight crime and terrorism. So, technology and privacy should be reconsidered. The researcher will analyze the Legal comprehension of privacy law in India and at global level & national level